Ursus arctos Linnaeus 1758 ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Ursus arctos Linnaeus, 1758 —Brown Bear Ursus arctos Linnaeus, 1758 p.47; Type locality- Sweden; Won, 1968 p.271; Han, 1994 p.46; Won & Smith, 1999 p.17; Oh, 2004a p.165. U. lasiotus Gray, 1867 p.301; Type locality- interior of northern China. Melanarctos cavifrons Heude, 1901 p.1; Type locality- northwestern Manchuria. U. cavifrons: Kishida & Mori, 1931 p.379. U. arctos lasiotus: Kuroda, 1938 p.31; Ellerman & Morrison-Scott, 1951 p.238; Won, 1958 p.440; Won, 1967 p.122; Won, 1968 p.273. U. arctos arctos: Yoon, 1992 p.99. Range: The distribution of U. arctos covers most northern alpine habitats and extends to the southern boundary at Mt. Geumgang (Kim et al. 2015; Fig. 40). Although this bear species was recorded around Mt. Baekdu until the 1980s, the current presence in the Mt. Geumgang and Mt. Baekdu areas in North Korea remains uncertain. Remarks: The Subspecies U. a. lasiotus Gray, 1867, Ussuri brown bear (or Amur brown bear, black grizzly or horse bear) in northeastern Asia traditionally ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 65, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...